League for the Popular Defence: the construction of a space of political struggle amongst organized workers in Porto Alegre after the General Strike of 1917 - Bartz, Frederico Duarte (2017)
http://dx.doi.org/10.5007/1984-9222.2016v8n16p117 The article analyses the formation and development League for the Defense of People's Porto Alegre (LDP), an organization created in 1917 to coordinate the general strike that broke out that year. The LDP was created under the influence of anarchist militants, but after the end of the strike movement, the League became a space for reformist syndicalists who ran the Workers' Federation, together with the Republican Party members, hold out their influence on organized workers of the state capital. As the LDP was a broad front, later this organization also served to the anarchist militants attack the reformist syndicalists and retake control of the Federation. Thus, the League will be understood in this article as a political battlefield, where militants from Porto Alegre faught for hegemony over the labor movement and control over their associations.